Analysis and design of space-time-frequency coded OFDM systems over frequency-selective fading channels - Capuno, Rex A. (2005)
This thesis investigates space-time-frequency (STF) coding for multiantenna orthogonal frequency division multiplexing (OFDM) transmissions over frequency-selective fading channels. This study provides a comparative analysis of the various types of STF codes introduced in the literature, namely, STF block, STF trellis, and differential STF (DSTF). Computer simulations show that all the schemes attain the same order of diversity but STF block and STF trellis codes achieve higher coding gains over DSTF codes. However, DSTF codes have the least decoding complexity since these codes do not require channel estimation, unlike STF block and STF trellis codes. STF trellis codes have the highest complexity because of the Viterbi algorithm used in decoding. STF block codes are the most favorable in terms of the trade-offs between performance and complexity. This thesis also presents a generalized method of designing STF codes through the use of spectral codes and space-time codes. From this design procedure, additional STF codes were proposed in this study and were shown to have comparable performance and complexity to the existing schemes. The proposed STF codes are based on the design from the literature but different spectral codes are utilized.
Thesis (M.S. Electrical Engineering : Computers and Communications)--University of the Philippines, Diliman.
Keywords: Wireless communication systems -- Design; Wireless communication systems; Orthogonal frequency division multiplexing